A hydrophilic inorganic framework based on a sandwich polyoxometalate: unusual chemoselectivity for aldehydes/ketones with in situ generated hydroxylamine. Issue 35 (16th August 2017) - Xing, Songzhu; Han, Qiuxia; Shi, Zhuolin; Wang, Shugai; Yang, PeiPei; Wu, Qiang; Li, Mingxue
Abstract : A green catalyst provides a synergistical catalytic way to synthesize an oxime from aldehyde/ketone by nucleophilic addition of in situ generated hydroxylamine and further promote its rearrangement into nitrile/amide in hydrosolvent. Abstract : A hydrophilic inorganic porous catalyst was prepared via the hydrothermal method. The combination of [WZn3 (H2 O)2 (ZnW9 O34 )2 ] 12− and Co(ii ) provides a synergistical catalytic way to promote oximation of aldehyde/ketone with in situ generated hydroxylamine that initially produces an oxime, which further either dehydrates into a nitrile or undergoes a Beckmann rearrangement to form an amide.